Ecological value of mariculture shellfish resources in China: Assessment and management. (February 2023) - Lin, Chun-Yu; Dai, Gui-Lin; Liu, Yang; Zhang, Meng-Qi; Liu, Ying; Jiang, Wen; Fu, Xiu-Mei; Chen, Han-Xue
Abstract: Under the background of global climate change and carbon reduction commitment, it is of great significance to study the ecological value of mariculture shellfish resources. China is the largest country in terms of mariculture shellfish. In this study, the ecological value of mariculture shellfish in China was dynamically evaluated after determining the shellfish ecological value composition and the value calculation coefficients. On this basis, the dynamic characteristics of the mariculture shellfish ecological values during 2010–2019 were revealed, as well as the economic problems and reasons behind. The study results indicated that the average ecological value of mariculture shellfish in China showed an overall upward trend. The core values of mariculture shellfish are carbon sequestration and water purification, which displayed an increasing trend. The habitat value of mariculture shellfish showed a significant downward trend because of the reduction of aquaculture area and the increase of aquaculture density. Additionally, the increase in the heavy metal enrichment value was due to the rising production of mariculture shellfish and the rising price of processing heavy metals in China. Therefore, innovative management policies were proposed including introducing a third-party independent consultant, building a carbon-sink shellfish demonstration zone, improving a carbon-sink market transaction mechanism, establishing a nitrogen credit market, and controlling the full-cycle management of mariculture shellfish based on biotechnology and blockchain technology. It was hoped to promote the healthy development of the mariculture shellfish industry and make China's contribution to the world's carbon emission reduction. Highlights: The ecological values of China's mariculture shellfish resources were assessed. The dynamic changing characteristics of the ecological value in China were revealed. The evaluation results were creatively applied to the shellfish management innovation. The economic reasons behind and management innovation were explored.